Polymyxin B Inadequately Quenches the Effects of Contaminating Lipopolysaccharide on Murine Dendritic Cells - Tynan, Graham A.; McNaughton, Anne; Jarnicki, Andrew; Tsuji, Takao; Lavelle, Ed C. (PLOS ONE, 2012)
Dendritic cell (DC) activation is commonly used as a measure of the immunomodulatory potential of candidate exogenous and endogenous molecules. Residual lipopolysaccharide (LPS) contamination is a recurring theme and the potency of LPS is not always fully appreciated. To address this, polymyxin B (PmB) is often used to neutralise contaminating LPS. However, the limited capacity of this antibiotic to successfully block these effects is neglected. Therefore, this study aimed to determine the minimum LPS concentration required to induce murine bone marrow-derived dendritic cell (BMDC) maturation and cytokine secretion and to assess the ability of PmB to inhibit these processes. LPS concentrations as low as 10 pg/ml and 20 pg/ml induced secretion of interleukin (IL)-6 and tumor necrosis factor (TNF)-α respectively, while a concentration of 50 pg/ml promoted secretion of IL-12p40. A much higher threshold exists for IL-12p70 as an LPS concentration of 500 pg/ml was required to induce secretion of this cytokine. The efficacy of PmB varied substantially for different cytokines but this antibiotic was particularly limited in its ability to inhibit LPS-induced secretion of IL-6 and TNF-α. Furthermore, an LPS concentration of 50 pg/ml was sufficient to promote DC expression of costimulatory molecules and PmB was limited in its capacity to reverse this process when LPS concentrations of greater than 20 ng/ml were used. There is a common perception that LPS is heat resistant. However, heat treatment attenuated the ability of low concentrations of LPS to induce secretion of IL-6 and IL-12p40 by BMDCs, thus suggesting that heat-inactivation of protein preparations is also an ineffective control for discounting potential LPS contamination. Finally, LPS concentrations of less than 10 pg/ml were incapable of promoting secretion of IL-6 independently but could synergise with heat-labile enterotoxin (LT) to promote IL-6, indicating that reducing contaminating endotoxin concentrations to low pg/ml concentrations is essential to avoid misleading conclusions regarding candidate immunomodulators.